1999
DOI: 10.1093/glycob/9.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation sites and site-specific glycosylation in human Tamm-Horsfall glycoprotein

Abstract: The N-glycosylation sites of human Tamm-Horsfall glycoprotein from one healthy male donor have been characterized, based on an approach using endoproteinase Glu-C (V-8 protease, Staphylococcus aureus ) digestion and a combination of chromatographic techniques, automated Edman sequencing, and fast atom bombardment mass spectrometry. Seven out of the eight potential N-glycosylation sites, namely, Asn52, Asn56, Asn208, Asn251, Asn298, Asn372, and Asn489, turned out to be glycosylated, and the potential glycosylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 38 publications
5
81
0
1
Order By: Relevance
“…Deglycosylation of THP-Purified human THP was reduced and Scarboxymethylated according to van Rooijen et al (45). THP was dissolved in 1 M Tris-HCl (pH 8.25) containing a final concentration of 50 mM dithiothreitol (Sigma), 6 M guanidine chloride, and 1 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…Deglycosylation of THP-Purified human THP was reduced and Scarboxymethylated according to van Rooijen et al (45). THP was dissolved in 1 M Tris-HCl (pH 8.25) containing a final concentration of 50 mM dithiothreitol (Sigma), 6 M guanidine chloride, and 1 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies have revealed UMOD expression to be exclusive to the renal epithelial cells lining the thick ascending limb of the loop of Henle and the early distal tubule (15). UMOD protein is glycosylated at 7 of its 8 potential N-glycosylation sites (16) and is glycosylphosphatidylinositol (GPI) anchored to the luminal surface of tubules, where it is cleaved into the urine at a rate of 50 to 100 milligrams per day (17), making it the most highly secreted protein in the urine of healthy individuals (18). In urine, it is found as a high-molecular-weight polymer (relative molecular weight [Mr] 1 × 10 6 to 10 × 10 6 ) and can be dissociated into monomers of roughly 95 kDa (17).…”
Section: Introductionmentioning
confidence: 99%
“…The localization of the spermligand active high-mannose-type chain in bovine ZPB and ZPC should be clarified. Besides the zona proteins, the ZP domain has been found in several proteins: TGF-b type III receptor (betaglycan) from fetal and adult tissues [28,29], uromodulin (urinary Tamm-Horsfall glycoprotein of pregnant woman) [30], the major zymogen granule membrane protein (GP-2) [31], and the proteins in the uterus and oviduct [32,33]. Furthermore, tectorins in the tectorial membranes responsible for hearing also have a ZP domain [34,35].…”
Section: Discussionmentioning
confidence: 99%